2015
DOI: 10.1016/j.nbd.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neuroprosthetics from a clinical perspective

Abstract: Recent pilot clinical studies have demonstrated that subjects with severe disorders of movement and communication can exert direct neural control over assistive devices using invasive Brain-Machine Interface (BMI) technology, also referred to as ‘cortical neuroprosthetics’. These important proof-of-principle studies have generated great interest among those with disability and clinicians who provide general medical, neurological and/or rehabilitative care. Taking into account the perspective of providers who m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…Arm movements accompanying BMI use are not expected in nearer-term clinical BMI systems 1 providing cursor control to people with paralysis or amputation. Nuisance variable mitigations such as Cursor Position Subtraction are therefore unnecessary in these applications, and we recommend against their use because such decoder operations introduce additional free parameters that are subject to neural non-stationarities or estimation errors, as noted in 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arm movements accompanying BMI use are not expected in nearer-term clinical BMI systems 1 providing cursor control to people with paralysis or amputation. Nuisance variable mitigations such as Cursor Position Subtraction are therefore unnecessary in these applications, and we recommend against their use because such decoder operations introduce additional free parameters that are subject to neural non-stationarities or estimation errors, as noted in 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…These systems read out the movement intentions of people with paralysis to restore function 1 , for example by controlling computer cursors for communication 2 , commanding arm and hand movements of robotic limbs 3 , or electrically stimulating the person’s own paralyzed muscles 4 . A key component of BMI systems is the decoder, which attempts to infer the user’s movement intentions from recorded neural activity 5 .…”
Section: Introductionmentioning
confidence: 99%
“…BMIs seek to restore lost function to people with neurological motor injury or disease by decoding neural activity from the brain to drive a prosthesis device, such as a computer cursor on a screen or a robotic arm (Bensmaia and Miller 2014; Ethier, Gallego, and Miller 2015; Homer et al 2013; Kao et al 2014; Tsu et al 2015). To date, substantial progress has been made in intracortical BMIs in which movement intention is inferred from electrical recordings of neurons in PMd and M1, enabling recent phase I clinical trials for translating this technology to humans (Collinger et al 2013; Gilja et al 2015; Hochberg et al 2006; Hochberg et al 2012; Wodlinger et al 2015).…”
Section: Insights From Optical Methods For Brain-machine Interface Dementioning
confidence: 99%
“…1, 2 Intracortical brain-machine interfaces (BMIs) have emerged as a promising clinical tool for restoring lost motor functions by translating neural activity directly into control signals for guiding assistive devices. 3,4 Early pilot clinical studies have demonstrated that BMIs can be used to control a computer cursor, 5-8 robotic arm, [9][10][11] or functional electrical stimulation (FES) system. [12][13][14] While there has been tremendous progress in the field of BMIs from both nonhuman primate and human studies in the past two decades, several challenges remain to be overcome to achieve a clinically viable translation of BMIs.…”
Section: Introductionmentioning
confidence: 99%